FROM THE HISTORY OF THE CONCEPT OF PHONEME - Juraevich, Zulkhanov Mustafo; Eshanovich, Mamatov Abdi; Abduvalievich, Yakubov Jamoldin; Boboevna, Davronova Zulfiya; Payziboyevich, Nishonov Pathiddin (International Journal of Psychosocial Rehabilitation, 2020)
The following article studies the history of the concept of phoneme, also scientific works on this direction. In particular, the article discusses problems of forming concept of phoneme.